Entrepreneurial Readiness: What Are The Roles Of Entrepreneurial Education, Environment And Student’s Mindset? - Pardiman, Pardiman; ABS, M. Khoirul (Technium Social Sciences Journal, 2020)
The objective of this study is to analyze students’ entrepreneurial readiness after taking Entrepreneurship course, which is a part of the educational curriculum, at their campuses. The data were obtained from questionnaires and processed in WarpPLS 5.0. The sample of this study is 323 students who have taken Entrepreneurial Education course. This study finds that Entrepreneurial Education will be more effective in affecting entrepreneurial readiness if the students’ mindset regarding entrepreneurship has been established. Furthermore, the mindset is affected by the entrepreneurship course and their environment. Therefore, this study suggests the necessity of shaping a more positive mindset towards entrepreneurship in students before they take entrepreneurship course.